Use of procalcitonin as a biomarker for sepsis in moderate to major paediatric burns. (July 2019) - Hollén, Linda; Hughes, Ryan; Dodds, Nick; Coy, Karen; Marlow, Karen; Pullan, Nicola; Davies, Julie; Dailami, Narges; Keating, Katrina; Falder, Sian; Shah, Mamta; Young, Amber
Introduction: Accurate and early detection of sepsis poses a significant challenge in burn populations. Our objective was to assess whether procalcitonin is a marker of blood culture positive sepsis in moderate to severe paediatric burns. Methods: We analysed procalcitonin levels in 27 children admitted with burns of 15–65% total body surface area. Procalcitonin was measured at admission (baseline), 24 and 48 h post-admission and during periods of suspected sepsis (diagnosed against pre-defined criteria). Patients were categorised into controls with no episodes of suspected sepsis ( n  = 10) and those with episodes of suspected sepsis ( n  = 17). The latter were split into two groups based on blood culture results: culture positive (bacteraemia) and culture negative patients. Results: Baseline procalcitonin levels increased with burn size (odds ratio (95% confidence interval): 1.15 (1.02–1.29)). Suspected sepsis patients had larger burns than controls (median 31 vs. 20%; p  = 0.003). Only 5/23 suspected sepsis episodes were blood culture positive. Procalcitonin levels were similar in culture positive and culture negative patients ( p  = 0.43). Sensitivity for predicting positive blood culture was 100% (95% confidence interval: 47.8–100.0%) but specificity was only 22.2% (95% confidence interval: 6.4–47.6%). Area under the curve was poor at 0.62 (95% confidence interval: 0.33–0.90). There was no significant change in procalcitonin levels from baseline to septic episode in either group (positive: p  = 0.35; negative: p  = 0.95). Conclusion: We conclude that evidence for the use of procalcitonin to diagnose bacteraemia in this population is poor, with burn size playing a significant role implying a correlation with systemic inflammation rather than sepsis.